Genetic Diversity and Population Structure of Indigenous Chicken Ecotypes (Gallus gallus domesticus) in Ethiopia using LEI0258 Microsatellite - Hailu , Addisu; Kyallo, Martina; Yohannes, Tilahun; Sendeku, Wagaw; Getu, Addis; Dagnachew, Shimelis; Dejen, Muluken; Wolde, Yidnekachew; Engdaw, Flipos; Kidane, Alayu; Dessie, Tadelle; Tarekegn, Getinet Mekuriaw; et al. (International Journal of Poultry Science, 2020)
Background and Objective: The indigenous chickens (Gallus gallus domesticus) are widely distributed all part of Ethiopia and remain as the main animal protein source for humans. Even though few marker-based molecular characterizations have been conducted on them, none of them used the LEI0258 microsatellite. Therefore, this research project was initiated to see the polymorphism of the LEI0258 microsatellite marker in the Ethiopian indigenous chickens and its potential to study indigenous chicken ecotypes. Materials and Methods: 2-5 mL of the blood sample was collected from 25-30 chicken per sample site. Then, total genomic DNA was extracted using a Qiagen DNA extraction kit followed by PCR amplification and Sanger sequencing. Results: Thirty-seven forms of LEI0258 were identified and the marker has been found as highly polymorphic with polymorphic information content (PIC) of 0.9288. The marker was employed to analyze the pairwise genetic distance between ecotypes. As a result, the lowest genetic distance was observed between Gema Gemmedaa and Ahun Tegegn ecotypes (0.4950). The highest genetic distance was observed between Sarbo and Gelego ecotypes (0.8324). The nine chicken ecotypes sampled in a different part of the country grouped into three major clusters. The naked neck chicken ecotype was isolated from the others and forms a separate cluster. Conclusion: The majority of LEI0258 microsatellite forms are found in at least in two ecotypes, although there are a few alleles unique to a particular ecotype.